2014
DOI: 10.1016/j.physleta.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-autonomous bright matter wave solitons in spinor Bose–Einstein condensates

Abstract: We investigate the dynamics of bright matter wave solitons in spin-1 Bose-Einstein condensates with time modulated nonlinearities. We obtain soliton solutions of an integrable autonomous three-coupled Gross-Pitaevskii (3-GP) equations using Hirota's method involving a non-standard bilinearization. The similarity transformations are developed to construct the soliton solutions of non-autonomous 3-GP system. The non-autonomous solitons admit different density profiles. An interesting phenomenon of soliton compre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…(10) and (11) (replacing c(t) withĉ(t)), we find that the intensity of first-and secondorder rogue waves comprises ofĉ(t) and t 0ĉ 2 (τ )dτ and in-turn depends on λγ as depicted in Eq. (34). It is clear from Fig.…”
Section: Management Of Matter Rogue Waves For the Class Of C(t) For Amentioning
confidence: 80%
See 1 more Smart Citation
“…(10) and (11) (replacing c(t) withĉ(t)), we find that the intensity of first-and secondorder rogue waves comprises ofĉ(t) and t 0ĉ 2 (τ )dτ and in-turn depends on λγ as depicted in Eq. (34). It is clear from Fig.…”
Section: Management Of Matter Rogue Waves For the Class Of C(t) For Amentioning
confidence: 80%
“…Recently, various studies have been reported that involve the study of solitons, rogue waves and their stability in BEC spinor system where the mean field interaction is attractive and the spin-exchange interaction is ferromagnetic. 15, 34,35 Being motivated by these studies we are considering the system with attractive mean-field interactions (c 0 < 0) and the ferromagnetic spin-exchange interactions (c 2 < 0). The corresponding autonomous model of Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The solution describing a standing breather on deep water was obtained in the class of Ptolemaic flows (6). This breather is created and evolves due to nonuniform pressure acting on the surface of the liquid.…”
Section: Resultsmentioning
confidence: 99%
“…This problem was initially considered in hydrodynamics and was later extended to other fields of physics [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the following section, with the knowledge of the bright one-and two-soliton solutions of the Manakov system (8) the non-autonomous bright soliton solutions of system (2) are obtained and their dynamical properties as well as their stability are discussed in detail. We would like to emphasize that the bright solitons of the Manakov system admit novel energy sharing collisions that have applications in optical computing [38,39], matter wave interferometer [40], and partially coherent solitons [41,42] of variable shape. Here we investigate these intriguing collisions in the presence of time dependent nonlinearity and Rabi coupling.…”
Section: Transforming Rabi Coupled Non-autonomous Gp System To the Mamentioning
confidence: 99%